Analisis Kadar Protein Tempe Dalam Kemasan Plastik - Ariana Agustin; Melisa Rusmalasari; Najwa Choirunnisa; Nurma Ayu Puspita; Liss Dyah Dewi Arini (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Tempe is the Indonesian people's favorite food. Tempeh, which is liked or commonly consumed, is a type of food made from yellow soybeans. These soybeans are fermented using the mold Rhizopus oligosporus. The results of this fermentation contain protein that is easily digested by the human body, making tempeh a food that is highly recommended for consumption in order to fulfill each individual's nutrition. However, this fermentation process is not so easy, it requires certain conditions. This is something that is often overlooked, so it is necessary to carry out research activities aimed at analyzing the protein content in plastic packaging. This protein content analysis activity uses the biuret method equipped with UV-Vis spectrophotometry with the standard protein solution used is BSA (Bovine Serum Albumin) solution. The measurements carried out provided information on the protein content of tempeh in plastic packaging of 3.739 µg/mL